Management of Young Blood Donors - Newman, Bruce H. (S. Karger GmbH, 2014)
The emphasis on high-school blood drives and acceptance of 16-year-old blood donors led to more research on physiologic and psychological ways to decrease vasovagal reaction rates in young blood donors and to increase donor retention. Research on how to accomplish this has been advantageous for the blood collection industry and blood donors. This review discussed the current situation and what can be done psychologically, physiologically, and via process improvements to decrease vasovagal reaction rates and increase donor retention. The donation process can be significantly improved. Future interventions may include more dietary salt, a shorter muscle tension program to make it more feasible, recommendations for post-donation muscle tension / squatting / laying down for lightheadedness, more donor education by the staff at the collection site, more staff attention to donors with fear or higher risk for a vasovagal reaction (e.g. estimated blood volume near 3.5 l, first-time donor), and a more focused donation process to ensure a pleasant and safer procedure.